Tax Planning Practices Amongst Tax Agents: Evidence from Malaysia - Palil, Mohd Rizal; Razif, Syahirah (Universitas Negeri Malang, 2022)
This study explored the complexity of corporate tax planning practised by the tax agents. In Malaysia, studies on tax investigations were limited due to the high information privacy factors. This study aimed to reveal the tax planning strategies through frequent adjustments made by the companies helped by the tax agents. Tax management itself is a way to properly meet the tax obligations, but the paid amount of tax can be reduced to obtain the expected profits. Tax planning leads and attracts more public attentions. A survey among 106 tax agents in Malaysia working in big-four companies revealed that tax planning appeared to be significant suggested by the tax agents as the companies had limited knowledge on tax regulations and law. This study also found an interesting finding in which companies heavily relied on the tax agents in minimising their yearly tax incidence although the tax planning might violate the current tax laws. This study recommends that the essential elements of designing a good tax system will help restrict the conditions which enable the tax evasion for the future development. This study considered the theoretical developments and related empirical findings on the interrelated issues to measure the tax planning and possible causes and results of corporate tax evasion. This study presented some ideas for further research to examine the unexplained topics on tax planning. In addition, the research findings also signaled to the policy makers to focus more on the integrity of tax agents to increase the compliance.